Biker and rocker styles in modern world fashion - Крічлоу, К. В.; Колосніченко, О. В.; Струмінська, Т. В.; Процик, Б. О.; Касс, Б. В. (Art and Design, 2021)
Study of the prerequisites of the emergence of Bikers and Rockers archetypes and their influence on the formation of corresponding subcultures and the direction of independent world fashion styles. The work uses a historical analysis and a visual-analytical method based on illustrative publications to study the artistic and compositional features of rider’s clothing. Based on the scientific works of K. Jung, the influence of the collective unconscious on the process of the emergence of "bikers" and "rockers" subcultures are determined. The prerequisites at the inception of these styles were considered, the development of rider’s clothing formation in world and Soviet’s fashion as artistic objects was studied, and the manifestations of compositional expressiveness were analysed. Scientific novelty consists in systematization of factors of occurrence of the classical biker style as an independent world fashion stream. Archetypical "bikers" and "rockers" have been identified and classified as part of subcultures and as a model of instinctive behaviour that exist in the collective unconscious. The practical significance consists in the analysis and theoretical generalization of materials that can be used in further applied scientific research of youth subcultures. The results are promising for further study of the influence of socially synthesized art on the clothing of drivers of motorized vehicles and on general trends in the development of world fashion.